The Calculation of Inelastic Zone Width of Coal Pillar in Highwall Mining With Backfill - Jiang, Juyu; Lu, Ye; Cao, Lanzhu; Wang, Dong; Wang, Laigui; Han, Xinping; Yang, Huiwen; Jia, Zhengzhao (Frontiers in Earth Science, 2022)
Highwall mining with backfill technology will be one of the main techniques of raising the recovery rate of coal resources under the end wall all over the world in the future, in which the coal pillar setting is the key to ensure the successful application of this technology, and the calculation for inelastic zone width of coal pillar has important guiding significance for the coal pillar setting in highwall mining with backfill. However, at present,in order to accurately calculate the inelastic zone width of coal pillar under the condition of highwall mining with backfill, a calculation model of inelastic zone width of highwall mining with backfill independent of empirical parameters is established by using limit equilibrium method, orthogonal experiment method, and nonlinear fitting method. In order to verify the correctness and reliability of the model, this paper takes the geological conditions of the Antaibao Open-pit Mine in Pingshuo, Shanxi Province, China, as the engineering background to verify the calculation accuracy of the model. The results show that the calculation model established in this paper can accurately calculate the inelastic zone width of the coal pillar under highwall mining with backfill and can meet the engineering needs.